Behavioral response of plaintive cuckoos (Cacomantis merulinus) to playback of conspecific vocalizations - YAUMUD RAIYARDHI; YENI ARYATI MULYANI; MIRZA DIKARI KUSRINI (Society for Indonesian Biodiversity, 2025)
Abstract. Raiyardhi Y, Mulyani YA, Kusrini MD. 2025. Behavioral response of plaintive cuckoos (Cacomantis merulinus) to playback of conspecific vocalizations. Biodiversitas 26: 2021-2027. The parasitic plaintive cuckoo (Cacomantis merulinus (Scopoli, 1786)) is difficult to study due to its elusive behavior. This research applied bioacoustic playback methods to explore the function of its vocalizations. The study, conducted at IPB University's Dramaga campus (267 ha) from March to August 2024, tested four different cuckoo sound patterns with varying amplitude (3-6 kU), frequency (2-4 kHz), and power (20-40 dB). Playback took place between 06:00 and 10:00 in known cuckoo territories, with each session followed by a 4-minute response observation. Spectrogram analysis and MANOVA were used to evaluate bird responses based on duration, amplitude, and frequency. Pattern A elicited communicative behavior and attracted the cuckoo to the sound source. Pattern B signaled territorial claims and competition, while pattern D functioned to repel other individuals. Pattern C had no effect, confirming that it was not a cuckoo call. MANOVA results demonstrated significant multivariate effects of playback type on the acoustic responses of the plaintive cuckoo, as shown by all four test statistics (e.g., Wilks’ Lambda: p = 0.017; Pillai’s Trace: p = 0.040). These results provide insight into conspecific communication within the family Cuculidae and demonstrate how vocalization types relate to behaviors such as attraction, territoriality, and defense.